The Trace of Memories of the Vietnam War: The Struggle Facing the Trauma in Shirley Ann Grau's "Homecoming" - Asri, Zietha; Sulistya Ningtyas (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
This study examines the trauma and memory associated with the Vietnam War experience in Shirley Ann Grau's short story "Homecoming," drawing on Paul Ricoeur’s narrative Theory, Maurice Halbwachs' Theory of collective memory, and Cathy Caruth's concept of trauma. The literary psychology approach analyzes how narration plays a role in individuals' struggle to confront trauma deeply rooted within. Specifically, Paul Ricoeur’s Theory is employed to depict the psychological struggle process in facing and overcoming trauma through narration as a medium of reflection and understanding of psychic wounds. Halbwachs' Theory explains how collective memory is formed by groups post-conflict, while Caruth's concept highlights trauma as an unresolved psychic wound profoundly affecting consciousness. The story portrays ongoing internal conflicts and wounds due to war trauma, as well as the crucial psychological struggle dynamics in the healing process. The findings affirm literature's vital role as a medium for reflecting historical memory, aiding post-conflict reconstruction, and enriching social interaction within society.